Development Of Renewal In Islamic Law And Human Rights In The Modern World - Fhadli Nur Hudzaifah (Al-Mahkamah: Islamic Law Journal, 2023)
Muslim countries are often trapped in a dilemma between being exclusive and maintaining the principles of Human Rights (HAM) outlined by Islam through Islamic law, or following the principles of human rights regulated internationally through the Universal Declaration of Human Rights. Islamic law and human rights must always be pursued to open wider opportunities for mutual understanding and in turn this will facilitate the achievement of progress and protection of human rights in Muslim countries. On the other hand, this dialogue is an important means for developing human rights discourse and eliminating the negative stigma towards Islamic law which is often accused of violating human rights, as well as opening up space for interpretation and study of Islamic law which continuously leads to the relevance of Islamic law in contemporary life. From an Islamic perspective, the concept of human rights is explained through the concept of maqâshid al-syarî'ah (goals of shari'ah), which has been formulated by past scholars. The aim of the shari'ah (maqâshid al-syarî'ah) is to realize the benefit (mashlahah) of mankind by protecting and realizing and protecting the things that are their necessity (dharûriyyât), as well as fulfilling the things that are their needs (hâjiyyât ) and their decoration (tahsîniyyât). For this reason, it is necessary to dialogue between human rights and Islamic law in order to reach a common understanding On the other hand, this dialogue is an important means for developing human rights discourse and eliminating the negative stigma towards Islamic law which is often accused of violating human rights, as well as opening up space for interpretation and study of Islamic law which continuously leads to the relevance of Islamic law in contemporary life.